Structure and microwave dielectric properties of Li(Al1-xLix)SiO4-x ceramics. Issue 3 (1st February 2023) - Wang, Yarong; Ding, Shihua; Hou, Zhengpeng; Xiao, Junwen; Zhang, Yun; Song, Tianxiu
Abstract: Li(Al1-x Lix )SiO4-x (x = 0.005, 0.01, 0.015, and 0.02) ceramics were synthesized via a traditional solid phase reaction method with different sintering temperatures. To determine the positions occupied by Li + in the lattice, the defect formation energies and total energies of various sites of LiAlSiO4 (LAS) occupied by Li + were examined, and the energy of LAS systems were calculated using density functional theory of first-principle with the CASTEP module. The results demonstrated that the Al-sites occupied by Li + had the lowest formation energies and total energy, so Li + should substitute Al 3+ . The impacts of replacing Al 3+ with Li + on the bulk density, sintering properties, phase composition, microstructure, and microwave dielectric properties of Li(Al1-x Lix )SiO4-x (0 = x ≤ 0.02) ceramics were thoroughly studied. With Li + -doping, the sintering temperature decreased from 1300 °C (x = 0) to 1175 °C (x = 0.02), while the Q × f and τ f values of LAS ceramics significantly increased. The Li(Al0.99 Li0.01 )SiO3.99 ceramic was fully sintered at 1250 °C for 10 h to obtain excellent microwave dielectric properties: ε r = 3.49, Q × f = 51, 358 GHz, and τ f = −51.48 × 10 −6 °C −1 .